Analisis Visual Branding Program Kelas Internasional Universitas Telkom Melalui Akun Instagram @Icaotelkomuniversity - Slamet Parsono; Aditya Ali (KOMVERSAL, 2025)
Instagram is now widely used by various groups. The function of this media is not only used for marketing business activities, but also for building corporate branding or personal branding. Telkom University International Class takes advantage of this opportunity by aggressively presenting the messages of its programs visually in order to help the sustainability of the media and remain of interest to the public. The purpose of this research is to analyze the branding of Telkom University's International Class program through the representation of visual messages displayed, find out how to build interaction through visual messages, and describe the compositions applied in the visual message of international class branding through the @icaotelkomuniversity Instagram account. The theory that underlies this research is social visual semiotics popularized by Carey Jewitt and Theo van Leewen. In contrast to general semiotics, this theory involves more semiotic sources to convey messages and actions in the form of image messages that can be interpreted. The method used in this research is a study of social visual semiotics with qualitative methods. The data collection technique is done by literature study and semiotically analyzing the visual messages of Instagram International Class Telkom University that have been documented.